1999
DOI: 10.1016/s0927-7757(98)00828-0
|View full text |Cite
|
Sign up to set email alerts
|

Streaming potential measurements as a characterization method for nanofiltration membranes

Abstract: The streaming potentials of two different nanofiltration membranes were studied with several electrolyte solutions to investigate the influence of salt type and concentration on the zeta potential and kinetic surface charge density of the membranes. The zeta potentials decreased with increasing salt concentration, whereas the kinetic surface charge densities increased. The kinetic surface charge densities could be described by Freundlich isotherms, except in one case, indicating that the membranes had a neglig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(66 citation statements)
references
References 23 publications
2
64
0
Order By: Relevance
“…Compared with the zeta potential measured in pure water which was much smaller for lower conduction in pure water, zeta potential commonly increased with the decrease of concentration [23][24][25] , which meant there was a peak value of zeta potential at a certain concentration between zero and 1 g·L −1 .…”
Section: Zeta Potential Measurement In Electrolytes Solutionsmentioning
confidence: 68%
See 1 more Smart Citation
“…Compared with the zeta potential measured in pure water which was much smaller for lower conduction in pure water, zeta potential commonly increased with the decrease of concentration [23][24][25] , which meant there was a peak value of zeta potential at a certain concentration between zero and 1 g·L −1 .…”
Section: Zeta Potential Measurement In Electrolytes Solutionsmentioning
confidence: 68%
“…Extensive research [23][24][25] has found that zeta potential of membranes increased with the decrease of electrolytes concentration. According to Helmholtz-Smoluchowski (H-S) equation, streaming potential increased with the decline of electrolyte concentration, while solution conductivity was just the opposite.…”
Section: Introductionmentioning
confidence: 99%
“…The graphs were based on a review of publications and therefore represent the MWCO dependence well. In NF combined charge and size effects are well recognised [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ionic strength of peptides solution affects the selectivity of NF membranes. In an aqueous medium the increase of the ionic strength, for example by the addition of NaCl, results in a decrease of zeta potential of the NF membrane [80][81][82][83] as well as a decrease in the electrophoretic mobility of proteins and peptides [84]. According to these observations, electrostatic interactions between the membrane and the peptides become less intense, which usually leads to better transmission values of the peptides.…”
Section: Main Parameters Influencing Peptide Fractionation Using Nf Mmentioning
confidence: 99%